Adaptation Of Workflow During Covid-19 Pandemic: A Malaysian Radiology Department's Experience - Assyifaa Nik Mazian; Norhaslinda Kamiso; Siti Soraya Ab Rahman (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 02-2021) [June 2021]